Mechanisms of fracture in 316L-TiC composite produced by selective laser melting - Cao, Chenguang (Nanyang Technological University, 2022)
By adding ceramic particles to the metal matrix, the metal matrix composites (MMC) could be prepared and ceramic particles have a good strengthening effect on metal materials. At the same time, the rapid development of selective laser melting (SLM) technology makes it possible to manufacture complex structures of composites rapidly and precisely. Therefore, in this work, the TiC particle reinforcement was introduced into the 316L matrix, and the 316L-TiC composite was prepared by the SLM process. The effects of different particle addition ratios (1 wt%, 3 wt%) and different input energies (225 W, 175 W) on the microstructure, mechanical properties, and fracture process are compared. Meanwhile, the reasons for the effects and the fracture mechanisms of different samples are summarized and discussed. By adding TiC particles, the melt pool of the printed sample is reduced, and the grains are refined. By adding 1 wt% and 3 wt% TiC particles, the yield strength of the material was increased to 660MPa and 832MPa, respectively. Lower laser printing power of 316L-3TiC led to a reduction both in yield strength and elongation (804 MPa and 10%). At the same time, the addition of TiC also changes the way of crack initiation and propagation. The crack initiation of the sample without TiC particles is mainly due to the accumulation of micro voids. For the samples with TiC particles, cracks initiated from broken TiC particles because of the brittleness of TiC particles. As for the low-energy printed samples, cracks were initiated and propagated from the formed cavities because of a lack of fusion.